(untitled) (Research, Society and Development, 2022)
Oxidative stress is associated with the pathogenesis of several chronic diseases. Cocoa is a food rich in polyphenols, with high antioxidant properties, and is an important food in its fight. However, most polyphenols have low solubility, which impairs their biological action. Therefore, encapsulation through the spray drying technique can significantly improve these parameters by generating a protective layer using proteins and polysaccharides. Therefore, the objective of this work was to elaborate a cocoa-based product encapsulated with maltodextrin (CM) or goat milk whey (CW) and to evaluate the total phenolic compounds and their antioxidant capacity, as well as the particle size of the encapsulated product. Cocoa-based products were encapsulated using maltodextrin DE20 or goat whey using a B-290 mini spray dryer (Büchi Labortechnik, Flawil, Switzerland) in a 1:1 weight ratio. Subsequently, the antioxidant capacity was analyzed by the 2,2’-azino-bis (3-ethylbenzoatiazoline-6-sulfonic acid) (ABTS) method and total phenolic compounds using the phenol reagent Folin-Ciocalteu by spectrophotometry, as well as the size of the particle. The CW obtained a higher yield (33.11%) when compared to the CM (24.03%) in the spray dryer. Most of the particles (90%) present in the CM and CS had a size of 21.92 and 21.12 µM, respectively. CW had a higher content of phenolic compounds compared to CM (CM: 536 ± 8.0 vs. CW: 818 ± 77.0 mg GAE/100g dw, p = 0.05). No significant difference was observed in antioxidant capacity between samples (CM: 545 ± 26.0 vs. CW: 478 ± 18.0 µmol TE/100g dw, p = 0.114). The results showed that although CS has a higher content of phenolic compounds, both had the same antioxidant capacity.